Feasibility study on the use of tangled metal wire particles as the adjustable elements in tuned mass dampers. (29th September 2019) - Tang, N.; Rongong, J.A.
Abstract: Tangled metal wire particles are a recent innovation that could provide an alternative to traditional damping materials. As they have low mass and are relatively insensitive to temperature, they are suitable for use in harsh environments. The present contribution demonstrates that these particles can be used as working elements for an adjustable Tuned Mass Damper. It is shown that the dynamic properties of a collection of tangled metal wire particles can be characterised with a reasonable accuracy, to provide the basis for a practical adjustable damper. The effectiveness of the new damper is demonstrated on two different vibration modes of a typical engineering structure. Finally, the new damper is shown to be much lighter than an equivalent tuned mass damper that was constructed more traditionally using polymeric O-rings.